Inter-organizational context of the innovation process and the role of architectural designers as system integrators: case evidence from Turkey - Erbil, Yasemin; Akıncıtürk, Nilüfer; Acar, Emrah (Informa UK Limited, 2013)
The construction industry is characterized as a complex product system industry. Complex product system projects require the temporary coalitions of organizations, efforts of which are coordinated by a specific type of organization called the ‘system integrator’. Although the traditional construction innovation literature assumes that the system integrator role is shared between the principal designer and principal contractor in a typical project, the complexity of built products may require the contribution of different types of system integrators, the roles of which may coincide over the life cycle of a project. An exploratory study was conducted to understand the extent to which architectural designers fulfil their system integrator role in the innovation process. In particular, the innovation-related information exchanges between architectural designers and other actors in their networks were the focus of interest. Face-to-face in-depth interviews were conducted to gather data from the owners/partners...